2020
DOI: 10.3390/rs12213566
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Using UAV Digital Photogrammetry in the Study of Slow-Moving Coastal Landslides

Abstract: The aim of this study is to demonstrate the advantages of using micro drones in the study of large slow-moving landslides, which are widespread along the northwestern coast of Malta. In particular, attention was given to the inventory and analysis of gravity-induced joints and megaclast deposits at four study sites selected due to the presence of remarkable examples of lateral spreads evolving into block slides. The research was carried out by means of Google Earth (GE) image analysis and uncrewed aerial vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 66 publications
0
29
0
1
Order By: Relevance
“…Uncrewed aerial vehicle digital photogrammetry (UAV-DP) is a robust methodology for the investigation of DGSDs and large landslides. In particular, it was used for the recognition of large lateral spreads in Malta and Tunisia [95,96]. We used UAV-DF and light detection and ranging (LiDAR) to extract high-resolution topographic 3D DGSD models and perform detailed morphometric analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Uncrewed aerial vehicle digital photogrammetry (UAV-DP) is a robust methodology for the investigation of DGSDs and large landslides. In particular, it was used for the recognition of large lateral spreads in Malta and Tunisia [95,96]. We used UAV-DF and light detection and ranging (LiDAR) to extract high-resolution topographic 3D DGSD models and perform detailed morphometric analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Mateos et al [17] reported an average velocity of the same order of magnitude (5.2 mm/yr) in a large lateral spreading along the North coast of Majorca (Spain). Extensive lateral spreading and block sliding processes in a geological setting comparable to the Chgega landslide have been under investigation since 2006 in the North part of Malta [8,9,[64][65][66]. In this area, long-term differential GNSS monitoring outputs carried out gave displacement rates between 0.8 and 2.4 cm/yr in a limestone plateau affected by lateral spreads and downslope blocks moved from block slides [64].…”
Section: Motion Detected In Chgega and In Other Similar Landslidementioning
confidence: 99%
“…UAVs, commonly called drones, provide indispensable help, efficiency in terms of speed and precision, as well as cost savings especially in inaccessible or difficult to navigate locations. UAVs are rising among many industries and have become very popular in numerous interdisciplinary researches, but for survey engineering they represent a quantum leap [36,37]. Several studies have demonstrated the usefulness and reliability of structure from motion (SfM) software and their implementation in landslide monitoring.…”
Section: Introductionmentioning
confidence: 99%